2019
DOI: 10.1016/j.omtn.2019.01.003
|View full text |Cite
|
Sign up to set email alerts
|

circRAPGEF5 Contributes to Papillary Thyroid Proliferation and Metastatis by Regulation miR-198/FGFR1

Abstract: The circular RNA RAPGEF5 (circRAPGEF5) is generated from five exons of the RAPGEF5 gene and abnormal expression in papillary thyroid cancer (PTC). However, whether circRAPGEF5 plays a role in PTC tumorigenesis remains unclear. The aim of the present study was to investigate the role of circRAPGEF5 in PTC. The results showed that circRAPGEF5 was upregulated in PTC tissues and cell lines. circRAPGEF5 knockdown inhibited cell proliferation, migration, and invasion in vitro ; and circRAPGEF5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 32 publications
(32 reference statements)
3
49
0
Order By: Relevance
“…And circRNA_102958 was significantly overexpressed in gastric cancer and it may be a potential novel and stable biomarker for the diagnosis of gastric cancer [13]. Besides, circRNA-RAPGEF5 contributes to papillary thyroid cancer cell proliferation, invasion, and migration [14]. Moreover, overexpressed circular RNA-MTO1 suppresses breast cancer cell viability and reverses monastrol resistan [15].…”
Section: Discussionmentioning
confidence: 99%
“…And circRNA_102958 was significantly overexpressed in gastric cancer and it may be a potential novel and stable biomarker for the diagnosis of gastric cancer [13]. Besides, circRNA-RAPGEF5 contributes to papillary thyroid cancer cell proliferation, invasion, and migration [14]. Moreover, overexpressed circular RNA-MTO1 suppresses breast cancer cell viability and reverses monastrol resistan [15].…”
Section: Discussionmentioning
confidence: 99%
“…And circRNA_102958 was signi cantly overexpressed in gastric cancer and it may be a potential novel and stable biomarker for the diagnosis of gastric cancer [13]. Besides, circRNA-RAPGEF5 contributes to papillary thyroid cancer cell proliferation, invasion, and migration [14]. Moreover, overexpressed circular RNA-MTO1 suppresses breast cancer cell viability and reverses monastrol resistan [15].…”
Section: Discussionmentioning
confidence: 99%
“…172 Likewise, low expression of circRAPGEF5 plays an important role in suppressing the aggressive biological behaviors of PTC by sponging miR-198, this subsequently downregulated the expression of fibroblast growth factor receptor 1 (FGFR1), a target gene of miR-198. 173 Moreover, overexpression of circ_0025033 promoted proliferation and invasion of PTC by directly sponging miR-1231 and miR-1304, therefore, circ_0025033/miR-1231/miR-1304 signaling pathway was considered to be a new regulatory mechanism in PTC initiation and progression. 174 Recent study found that knockdown of circRNA_102171 inhibited PTC progression.…”
Section: Papillary Thyroid Carcinomamentioning
confidence: 99%